Do girls pay the price of civil war? Violence and infant mortality in Congo - Dagnelie, Olivier; De Luca, Giacomo; Maystadt, Jean-François (International Food Policy Research Institute, 2014)
This paper documents the impact of the violent civil war affecting the Democratic Republic of Congo in the period 1997–2004 on infant mortality. It adopts an instrumental variable approach to correct for the nonrandom timing and location of conflict events using mineral price index variations by district, taking account of the mineral locations and prices, as instrument. Strong and robust evidence, including mother fixed effects regressions comparing siblings, shows that conflict significantly increases girl mortality. The paper also examines the mechanisms explaining this phenomenon, with a focus on disentangling the behavioral from the biological factors. The analysis suggests that gender imbalances in infant mortality are driven by the selection induced by a higher vulnerability of boys in utero rather than by gender discrimination.